Difference between revisions of "022 Sample Final A, Problem 1"

From Math Wiki
Jump to navigation Jump to search
 
(7 intermediate revisions by the same user not shown)
Line 1: Line 1:
<span class="exam">Find all first and second partial derivatives of the following function, and demostrate that the mixed second partials are equal for the function <math> f(x, y) = \frac{2xy}{x-y}.</math>
+
<span class="exam">Find all first and second partial derivatives of the following function, and demostrate that the mixed second partials are equal for the function <math style="vertical-align: -17px"> f(x, y) = \frac{2xy}{x-y}.</math>
  
  
Line 5: Line 5:
 
!Foundations: &nbsp;  
 
!Foundations: &nbsp;  
 
|-
 
|-
|1)Which derivative rules do you have to use for this problem?
+
|1) Which derivative rules do you have to use for this problem?
 
|-
 
|-
|2)What is the partial derivative of xy, with respect to x?
+
|2) What is the partial derivative of <math style="vertical-align: -4px">xy</math>, with respect to <math style="vertical-align: 0px">x</math>?
 
|-
 
|-
|1)You have to use the quotient rule, and product rule. The quotient rule says that <math>\frac{\partial}{\partial x} \left(\frac{f(x)}{g(x)}\right) = \frac{f'(x)g(x) - g'(x)f(x)}{g(x)^2}</math>, &nbsp; so <math>\frac{\partial}{\partial x} \left(\frac{x^2}{x + 1}\right) = \frac{2x(x + 1) - x^2}{(x + 1)^2}</math>. The product rule says <math>\frac{\partial}{\partial x} f(x)g(x) = f'(x)g(x) + g'(x)f(x) </math>. &nbsp; This means <math>\frac{\partial}{\partial x} x(x + 1) = (x + 1) + x </math>
 
 
|-
 
|-
|2) The partial derivative is y, since we treat anything not involving x as a constant and take the derivative with respect to x. So <math>\frac{\partial}{\partial y} xy = x\frac{\partial}{\partial y} y = x.</math>
+
|Answers:
 +
|-
 +
|1) You have to use the quotient rule and product rule. The quotient rule says that
 +
::<math style="vertical-align: 0px">\frac{\partial}{\partial x} \left(\frac{f(x)}{g(x)}\right) = \frac{f'(x)g(x) - g'(x)f(x)}{g(x)^2},</math>
 +
so
 +
::<math style="vertical-align: 0px">\frac{\partial}{\partial x} \left(\frac{x^2}{x + 1}\right) = \frac{2x(x + 1) - x^2}{(x + 1)^2}.</math>
 +
The product rule says
 +
::<math style="vertical-align: 0px">\frac{\partial}{\partial x} f(x)g(x) = f'(x)g(x) + g'(x)f(x). </math>
 +
This means
 +
::<math style="vertical-align: 0px">\frac{\partial}{\partial x} [x(x + 1)] = (x + 1) + x. </math>
 +
|-
 +
|2) The partial derivative is <math style="vertical-align: -4px">y</math>, since we treat anything not involving <math style="vertical-align: 0px">x</math> as a constant and take the derivative with respect to <math style="vertical-align: 0px">x</math>. In more detail, we have
 +
::<math style="vertical-align: 0px">\frac{\partial}{\partial x} xy \,=\, y\frac{\partial}{\partial x} x \,=\, y.</math>
 
|}
 
|}
  
 
'''Solution:'''
 
'''Solution:'''
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
!Foundations: &nbsp;  
+
!Step 1: &nbsp;
 +
|-
 +
|First, we start by finding the first partial derivatives. So we have to take the partial derivative of <math style="vertical-align: -4px">f(x, y)</math> with respect to <math style="vertical-align: 0px">x</math>, and the partial derivative of <math style="vertical-align: -4px">f(x, y)</math> with respect to <math style="vertical-align: -4px">y</math>. This gives us the following:
 +
|-
 +
|
 +
::<math>\begin{array}{rcl}
 +
\displaystyle{\frac{\partial}{\partial x} f(x, y)} & = & \displaystyle{\frac{\partial}{\partial x} \left( \frac{2xy}{x - y}\right)}\\
 +
&&\\
 +
& = & \displaystyle{\frac{2y(x - y) -2xy}{(x - y)^2}}\\
 +
&&\\
 +
& = & \displaystyle{\frac{-2y^2}{(x - y)^2}.}
 +
\end{array}</math>
 +
|-
 +
|This gives us the derivative with respect to <math style="vertical-align: 0px">x</math>. To find the derivative with respect to <math style="vertical-align: -4px">y</math>, we do the following:
 +
|-
 +
|
 +
::<math>\begin{array}{rcl}
 +
\displaystyle{\frac{\partial}{\partial y}f(x, y)} & = & \displaystyle{\frac{\partial}{\partial y}\left(\frac{2xy}{x - y}\right)}\\
 +
&&\\
 +
& = & \displaystyle{\frac{2x(x - y) +2xy}{(x - y)^2}}\\
 +
&&\\
 +
& = & \displaystyle{\frac{2x^2}{(x - y)^2}.}
 +
\end{array}</math>
 +
|}
 +
 
 +
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 +
!Step 2: &nbsp;
 +
|-
 +
|Now we have to find the 4 second derivatives,  We have
 +
<br>
 +
::<math>\begin{array}{rcl}
 +
\displaystyle{\frac{\partial^2f(x,y)}{\partial x^2}\,=\,\frac{\partial}{\partial x} \left(\frac{\partial f(x, y)}{\partial x}\right)} & = & \displaystyle{\frac{\partial}{\partial x}\left(\frac{-2y^2}{(x - y)^2}\right)}\\
 +
&&\\
 +
& = & \displaystyle{\frac{0 - 2(x - y)(-2y^2)}{(x - y)^4}}\\
 +
&&\\
 +
& = & \displaystyle{\frac{4xy^2 - 4y^3}{(x - y)^4}.}
 +
\end{array}</math>
 +
|-
 +
|Also,
 +
<br>
 +
::<math>\begin{array}{rcl}
 +
\displaystyle{\frac{\partial^2f(x,y)}{\partial y\partial x}\,=\,\frac{\partial}{\partial y} \left(\frac{\partial f(x, y)}{\partial x}\right)} & = & \displaystyle{\frac{\partial}{\partial y}\left(\frac{-2y^2}{(x - y)^2}\right)}\\
 +
&&\\
 +
& = & \displaystyle{\frac{-4y(x - y)^2 -4y^2(x - y)}{(x - y)^4}}\\
 +
&&\\
 +
& = & \displaystyle{\frac{-4y(x^2 - 2xy + y^2) - 4xy^2 + 4y^3}{(x - y)^4}}\\
 +
& = & \displaystyle{\frac{4xy^2 - 4x^2y}{(x - y)^4}.}
 +
\end{array}</math>
 +
|-
 +
|Showing the equality of mixed partial derivatives,
 +
<br>
 +
::<math>\begin{array}{rcl}
 +
\displaystyle{\frac{\partial^2f(x,y)}{\partial x\partial y}\,=\,\frac{\partial}{\partial x} \left(\frac{\partial f(x, y)}{\partial y}\right)} & = & \displaystyle{\frac{\partial}{\partial x}\left(\frac{2x^2}{(x - y)^2}\right)}\\
 +
&&\\
 +
& = & \displaystyle{\frac{4x(x - y)^2 -2(x - y)2x^2}{(x - y)^4}}\\
 +
&&\\
 +
& = & \displaystyle{\frac{4x(x^2 - 2xy + y^2) -4x^3+ 4x^2y}{(x - y)^4}}\\
 +
&&\\
 +
& = & \displaystyle{\frac{4xy^2 -4x^2y}{(x - y)^4}.}
 +
\end{array}</math>
 +
|-
 +
|Finally,
 +
<br>
 +
::<math>\begin{array}{rcl}
 +
\displaystyle{\frac{\partial^2f(x,y)}{\partial y^2}\,=\,\frac{\partial}{\partial y} \left(\frac{\partial f(x, y)}{\partial y}\right)}  & = & \displaystyle{\frac{\partial}{\partial y}\left(\frac{2x^2}{(x - y)^2}\right)}\\
 +
&&\\
 +
& = & \displaystyle{\frac{0 + 2(x - y)(2x^2)}{(x - y)^4}}\\
 +
&&\\
 +
& = & \displaystyle{\frac{4x^3 - 4x^2y}{(x - y)^4}.}
 +
\end{array}</math>
 +
|}
 +
 
 +
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 +
!Final Answer: &nbsp;  
 
|-
 
|-
|The word 'marginal' should make you immediately think of a derivative.  In this case, the marginal is just the partial derivative with respect to a particular variable.
+
|The first partial derivatives are:
 +
::<math>\displaystyle{\frac{\partial}{\partial x} f(x, y) = \frac{-2y^2}{(x - y)^2}, \qquad
 +
\frac{\partial}{\partial y} f(x, y) = \frac{2x^2}{(x - y)^2}.}</math>
 
|-
 
|-
|The teacher has also added the additional restriction that you should not leave your answer with negative exponents.
+
|The second partial derivatives are:
 +
::<math>\frac{\partial^{2}f(x,y)}{\partial x^{2}}\,=\,\frac{4xy^{2}-4y^{3}}{(x-y)^{4}},
 +
\qquad\frac{\partial^{2}f(x,y)}{\partial x\partial y}\,=\,\frac{\partial^{2}f(x,y)}{\partial y\partial x}\,=\,\frac{4xy^{2}-4x^{2}y}{(x-y)^{4}},\qquad\frac{\partial^{2}f(x,y)}{\partial y^{2}}\,=\,\frac{4x^{3}-4x^{2y}}{(x-y)^{4}}.</math>
 
|}
 
|}
 +
[[022_Sample_Final_A|'''<u>Return to Sample Exam</u>''']]

Latest revision as of 08:20, 7 June 2015

Find all first and second partial derivatives of the following function, and demostrate that the mixed second partials are equal for the function


Foundations:  
1) Which derivative rules do you have to use for this problem?
2) What is the partial derivative of , with respect to ?
Answers:
1) You have to use the quotient rule and product rule. The quotient rule says that

so

The product rule says

This means

2) The partial derivative is , since we treat anything not involving as a constant and take the derivative with respect to . In more detail, we have

Solution:

Step 1:  
First, we start by finding the first partial derivatives. So we have to take the partial derivative of with respect to , and the partial derivative of with respect to . This gives us the following:
This gives us the derivative with respect to . To find the derivative with respect to , we do the following:
Step 2:  
Now we have to find the 4 second derivatives, We have


Also,


Showing the equality of mixed partial derivatives,


Finally,


Final Answer:  
The first partial derivatives are:
The second partial derivatives are:

Return to Sample Exam